Survey on Mobile Optimized Search Crawler - Kajal, Kukreja; Nishigandha, Gavali; Gandhali, Khedlekar (International Journal of Computer Sciences and Engineering, 2025)
The web crawler is the central component of a search engine which works like an indexer, finds out hyperlinks and computes keyword density of each web page. It assigns a page rank to each crawled web page by using some ranking algorithm and stores the visited links for the future use. Search results retrieve very fast from desktop browser, but it takes more time when user is on mobile. When a keyword is searched from a mobile browser, the traditional web servers take a long time to interpret this request. Also, the web server has to format search results into the form which mobile device can interpret. Thus, to eliminate this overhead on the web server, a Mobile Application Server has to be introduced instead of the web server to interpret requests from mobile devices